Integrated assessment of marine biodiversity status using a prototype indicator-based assessment tool - Andersen, Jesper H.; Dahl, Karsten; Göke, Cordula; Hartvig, Martin; Murray, Ciarán; Rindorf, Anna; Skov, Henrik; Vinther, Morten; Korpinen, Samuli (Frontiers in Marine Science, 2014)
Integrated assessment of the status of marine biodiversity is and has been problematic compared to, for example, assessments of eutrophication and contamination status, mostly as a consequence of the fact that monitoring of marine habitats, communities and species is expensive, often collected at an incorrect spatial scale and/or poorly integrated with existing marine environmental monitoring efforts. The objective of this Method Paper is to introduce and describe a simple tool for integrated assessment of biodiversity status based on the HELCOM Biodiversity Assessment Tool (BEAT), where interim biodiversity indicators are grouped by themes: broad-scale habitats, communities, and species as well as supporting non-biodiversity indicators. Further, we report the application of an initial indicator-based assessment of biodiversity status of Danish marine waters where we have tentatively classified the biodiversity status of Danish marine waters. The biodiversity status was in no areas classified as ‘unaffected by human activities’. In all the 22 assessment areas, the status was classified as either ‘moderately affected by human activities’ or ‘significantly affected by human activities. Spatial variations in the biodiversity status were in general related to the eutrophication status as well as fishing pressure.